Investigations on rutting potential and performance specifications for Marshall designed bituminous mixtures - Shaikh S.; Gupta A.; Saboo N. (My University, 2025)
The objective of this study was to assess the impact of various design factors and volumetric parameters on the rutting performance of bituminous mixtures. A dynamic creep test was performed using the dynamic testing system to evaluate the rutting resistance. The test results showed that higher rutting resistance can be achieved using a higher nominal maximum size of the aggregate (NMAS), coarser gradation, modified binder and increased compaction effort. Also, it was found that among the different volumetric parameters, higher Gmb and VFA contribute to lower permanent strain (%) while increased air void and VMA correlate with higher permanent strain (%). Additionally, linear regression models were developed to predict permanent strain (%) based on the design factors and volumetric properties considered in the study. Furthermore, the present study establishes and validates the threshold values of permanent strain for the selection of rut-resistant bituminous mixtures. © 2024 Informa UK Limited, trading as Taylor & Francis Group.